2020
DOI: 10.3390/rs12081245
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Forest Growing Stock Volume with UAV Laser Scanning Data: Can It Be Done without Field Data?

Abstract: Laser scanning data from unmanned aerial vehicles (UAV-LS) offer new opportunities to estimate forest growing stock volume ( V ) exclusively based on the UAV-LS data. We propose a method to measure tree attributes and using these measurements to estimate V without the use of field data for calibration. The method consists of five steps: i) Using UAV-LS data, tree crowns are automatically identified and segmented wall-to-wall. ii) From all detected tree crowns, a sample is taken where diameter at brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…All the remaining surface points were then interpolated by triangulated irregular networks. Many studies have generated CHM from UAVLS data with various spatial resolutions, ranging 0.1 to 1 m [10,16,49,50]. Yin and Wang (2019) have recommended that spatial resolution should be finer than one fourth of the crown diameter to correctly delineate crown boundaries and characterize the crown shapes.…”
Section: Uavls Data Preprocessingmentioning
confidence: 99%
“…All the remaining surface points were then interpolated by triangulated irregular networks. Many studies have generated CHM from UAVLS data with various spatial resolutions, ranging 0.1 to 1 m [10,16,49,50]. Yin and Wang (2019) have recommended that spatial resolution should be finer than one fourth of the crown diameter to correctly delineate crown boundaries and characterize the crown shapes.…”
Section: Uavls Data Preprocessingmentioning
confidence: 99%
“…Ni et al (2015) reported exceptional levels of accuracy when calculating tree heights, and Alonzo et al (2018) achieved similar accuracies when modelling tree density, basal area, aboveground biomass, and species composition in boreal conditions. While UAV-based forest inventories are limited to small areas due to the high cost, they could be particularly effective, for example, in predicting the diameter distribution or in the determination of ℎ (Puliti et al 2020).…”
Section: Simplifying the Cross-bioregional Assessment Of Fst (Ii)mentioning
confidence: 99%
“…Besides the further integration of remotely sensed data (Solberg et al 2019 ; Puliti et al 2020a , b ), NFI researchers also work on improved tree-level assessments through terrestrial (Ducey and Astrup 2013 ; Astrup et al 2014 ) or drone-based scanning techniques (Puliti et al 2019 , 2020a , b ). We perceive the great potential of these relatively new measurement techniques in documenting the vegetation status, which enables new measurements at a later stage and provides additional information, for example on stem and crown shapes (e.g.…”
Section: Current Developments and The Foreseeable Futurementioning
confidence: 99%